Avian species richness and abundance show stronger responses to bison grazing intensity than to ecosystem productivity - Danielle A. Fagre; William M. Janousek; Victoria J. Dreitz (Ecosphere, 2022)
Abstract Temperate grassland ecosystems are one of the most threatened ecosystems worldwide, and their loss endangers the grassland songbirds that rely upon them. This guild of birds has shown long‐term declines in North America. At the same time, American bison (Bison bison) are becoming more common through reintroductions, and they may make significant modifications to grassland songbird habitat. To support conservation for this guild, we sought to understand the importance of bison grazing and ecosystem productivity to the species richness, occupancy, and abundance of this avian community. We conducted dependent double‐observer bird counts, measured bison grazing intensity with patty counts, and used remote‐sensed normalized difference vegetation index (NDVI) data to measure ecosystem productivity. Our work took place in the National Bison Range near Moiese, Montana and in Yellowstone National Park in Wyoming. We found that species richness was positively correlated with patty counts and had a weak negative correlation with NDVI. Occupancy probability for six of seven grassland songbird species was positively correlated with patty counts, and for six of seven species was negatively correlated with NDVI. Abundance of vesper sparrow (Pooecetes graminueus) and western meadowlark (Sturnella neglecta) were positively correlated with patty counts, although for western meadowlark, this trend became less positive with increasing patty counts. Our work suggests that managers may want to encourage a broad range of bison grazing intensities to ensure that vegetative conditions related to bison grazing are present for all species.